2022
DOI: 10.1248/bpb.b22-00206
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Encapsulated in Exosomes Derived from Platelet-Rich Plasma Promotes Chondrogenic Differentiation of the Bone Marrow Mesenchymal Stem Cells <i>via</i> the Wnt/β-Catenin Pathway

Abstract: Cartilage regenerative medicine, wherein the stem cells from adults exert a crucial role, has high potential in the treatment of defective articular cartilage. Recently, Bone marrow mesenchymal stem cells (BMSCs) are being increasingly recognized as an alternative source of adult stem cells, which are capable of differentiating into several cell types (e.g., adipocytes, chondrocytes, and osteoblasts). However, their proliferative properties and tendency to dedifferentiate restrict their use in clinical setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…According to all reported works compiled in this review, PRP-EVs represent a promising therapeutic approach in the field of tissue repair and regeneration. PRP-EVs promoted cell proliferation and migration [31,34,35,[40][41][42][45][46][47][48][49][50] and angiogenesis [35,45,50] while reducing the inflammatory response [31][32][33]41,42], apoptosis [31,34,41,42,50] the oxidative stress [41] and senescence [41], among others. PRP-EVs seem to exert their function through different signaling pathways such as Wnt/β-catenin [31,47,50], AKT/ERK [35,45], TLR4 [39], PI3K/Akt [40], PGC1α-TFAM [41], Keap1-Nrf2 [42], YAP [45] and Akt/Bad/Bcl-2 [50].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…According to all reported works compiled in this review, PRP-EVs represent a promising therapeutic approach in the field of tissue repair and regeneration. PRP-EVs promoted cell proliferation and migration [31,34,35,[40][41][42][45][46][47][48][49][50] and angiogenesis [35,45,50] while reducing the inflammatory response [31][32][33]41,42], apoptosis [31,34,41,42,50] the oxidative stress [41] and senescence [41], among others. PRP-EVs seem to exert their function through different signaling pathways such as Wnt/β-catenin [31,47,50], AKT/ERK [35,45], TLR4 [39], PI3K/Akt [40], PGC1α-TFAM [41], Keap1-Nrf2 [42], YAP [45] and Akt/Bad/Bcl-2 [50].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Studies in various fields have found that PRP can promote cell proliferation and migration ( 61 , 62 ), angiogenesis ( 63 , 64 ), and reduce inflammatory reactions, oxidative stress, and aging ( 65 , 66 ). In addition, research has found that PRP appears to function through different signaling pathways, such as AKT/ERK ( 63 , 64 ), PGC1 α- TFAM ( 65 ), Keap1-Nrf2 ( 66 ), Wnt/β- Chain proteins ( 67 ), TLR4 ( 68 ), PI3K/Akt ( 69 ), and Akt/Band/Bcl-2 ( 70 ). However, there is still a lack of research on the pathways involved in PRP promoting ovarian regeneration and improving POR, and further research is needed to elucidate its related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent physical methods include: co-incubation, electroporation, sonication, mechanical extrusion, etc (Figure 4A) (Haney et al, 2015). All of these methods can deliver cargos to exosomes such as miRNA, siRNA, proteins, lipophilic drugs like curcumin (Cur) (Lin et al, 2018;Guo et al, 2019;Pomatto et al, 2019;He et al, 2020;Wang et al, 2021), and water-soluble drugs like berberine (Table 2) (Dong et al, 2022). Therapeutic miRNA and proteins are usually loaded into exosomes using endogenous loading methods, while small molecule cargos are mainly loaded using exogenous loading methods, sometimes endogenous and exogenous methods can be combined to produce engineering exosomes.…”
Section: Different Methods For Preparation Of Engineering Exosomesmentioning
confidence: 99%